Organic anion transporting polypeptide 1a/1b–knockout mice provide insights into hepatic handling of bilirubin, bile acids, and drugs - van de Steeg, Evita (American Society for Clinical Investigation, 2010)
Organic anion transporting polypeptides (OATPs) are uptake transporters for a broad range of endogenous compounds and xenobiotics. To investigate the physiologic and pharmacologic roles of OATPs of the 1A and 1B subfamilies, we generated mice lacking all established and predicted mouse Oatp1a/1b transporters (referred to as Slco1a/1b(–/–) mice, as SLCO genes encode OATPs). Slco1a/1b(–/–) mice were viable and fertile but exhibited markedly increased plasma levels of bilirubin conjugated to glucuronide and increased plasma levels of unconjugated bile acids. The unexpected conjugated hyperbilirubinemia indicates that Oatp1a/1b transporters normally mediate extensive hepatic reuptake of glucuronidated bilirubin. We therefore hypothesized that substantial sinusoidal secretion and subsequent Oatp1a/1b-mediated reuptake of glucuronidated compounds can occur in hepatocytes under physiologic conditions. This alters our perspective on normal liver functioning. Slco1a/1b(–/–) mice also showed drastically decreased hepatic uptake and consequently increased systemic exposure following i.v. or oral administration of the OATP substrate drugs methotrexate and fexofenadine. Importantly, intestinal absorption of oral methotrexate or fexofenadine was not affected in Slco1a/1b(–/–) mice. Further analysis showed that rifampicin was an effective and specific Oatp1a/1b inhibitor in controlling methotrexate pharmacokinetics. These data indicate that Oatp1a/1b transporters play an essential role in hepatic reuptake of conjugated bilirubin and uptake of unconjugated bile acids and drugs. Slco1a/1b(–/–) mice will provide excellent tools to study further the role of Oatp1a/1b transporters in physiology and drug disposition.